Percentage of Carcass and Protein Content of Breast Meat of Native Chicken Given Apu-Apu Flour (Pistia stratiotes) - Muhammad Basri; Muhammad Nur Hidayat; R. Rusny (Chalaza Journal of Animal Husbandry, 2020)
The research aimed to determine the percentage of carcass and protein content of super native chicken breast meat given rations containing apu-apu flour (Pistia stratiotes). The research design used was completely randomized design (C.R.D.) with five treatments and three replications.  Each test consisted of three super three-month-old native chickens. Apu-apu flour levels in each treatment, namely P0 (0%), P1 (5%), P2 (10%), P3 (15%) and P4 (20%). The study was conducted for four weeks. The percentage of carcasses in each treatment were P0 (67.51%), P1 (69.33%), P2 (69.47%), P3 (68.76%) and P4 (70.88%). Furthermore, protein content in breast meat, namely P0 (25.21%), P1 (26.03%), P2 (25.43%), P3 (25.86%) and P4 (25.35%).  There were no significant effects (P 0.05) of fluorine in rations on the carcass percentage and protein content of super native chicken breast meat. The highest average value of carcass percentage was in the treatment of 20% Pistia stratiotes flour, while the highest breast meat protein content was in the treatment of 5% Pistia stratiotes flour.